Opuść nawiasy i zredukuj wyrazy podobne:

a) (3x+4y+2z)-(-2x+4y-5z)-(x+3y-2z)=
b) (x-2y-3z)-(3x+2y+z)+(4x-3y-3z)=
c) (3-2x+4x²-2x³)+(-x³-2x²-2x-6)=
d) 3(2a-b)-5(1/10a-4b)-(4a-10b):2=

Oblicz po doprowadzeniu do najprostszej postaci:

a= -3½
b= 1⅓

(2a-3b)-(4a+2b)-(-7a+4b)=

1

Odpowiedzi

2010-03-25T16:21:36+01:00
A) (3x+4y+2z) - (-2x+4y-5z) - (x+3y-2z)
= 3x +4y +2z +2x -4y + 5z -x -3y + 2z=
=4x - 3y + 9z

b) (x-2y-3z) - (3x+2y+z) + (4x-3y-3z)
=x - 2y - 3z -3x -2y - z + 4x - 3y - 3z
= 2x - 7y - 7z

c) -(x^2-3x+2) + (4-3x+2x^2) - (7+4x-3x^2)

d) -(3-2x+4x^2-2x^3)+(-x^3-2x^2-2x-6)
= -3 +2x - 4x^2 + 2x^3 - x^3 - 2x^2 - 2x - 6
= - 9 -6x^2 + x^3

^- to do potegi 2





4 5 4